INFLUENCE OF THE RATE OF SEED DRAPING WITH BENTONITE CLAY AND IRRIGATION REGIME ON THE FORMATION OF THE ROOT SYSTEM OF WINTER WHEAT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In this article, under the conditions of light gray soil of the Kashkadarya region, as a result of the influence of the method of covering the seeds of winter wheat varieties with bentonite clay and irrigation methods on the rood mass, in the Shukron variety up to 32,9-54,2 g and in the Turon variety up to 40,2-68 g.